MAPPING THE RESEARCH LANDSCAPE OF SAKIP IN INDONESIA: A BIBLIOMETRIC ANALYSIS - Hasmi Nasution; Intan Oktoviona; Mawar Dayu Afmi Risky; Syed Agung Afandi (Madani Connection, 2026)
Abstract This study aims to analyze the development and research trends of the Government Agency Performance Accountability System (SAKIP) in Indonesia using a bibliometric approach. SAKIP is a key instrument in Indonesia's bureaucratic reform and has attracted significant academic attention over the past two decades. Through the analysis of 205 articles published between 1999 and 2026 sourced from Google Scholar using the Publish or Perish software, this study maps publication growth patterns, keyword networks, and dominant thematic clusters using VOSviewer. Results indicate significant and consistent publication growth, particularly since 2017, with dominant keywords including sakip, accountability, performance accountability, and government agency performance accountability system. Bibliometric network analysis identified four main thematic clusters reflecting the complexity of SAKIP studies from the perspectives of implementation, performance measurement, information technology, and human resources. These findings make an important contribution to the development of future SAKIP research agendas and policy implications for strengthening performance-based governance in Indonesia.